Plasma small extracellular vesicles from dogs affected by cutaneous mast cell tumors deliver high levels of miR-21-5p - Zamboni, Clarissa; Zamarian, Valentina; Stefanello, Damiano; Ferrari, Roberta; Auletta, Luigi; Milanesi, Samantha; Mauri, Samuele; Grieco, Valeria; Ceciliani, Fabrizio; Lecchi, Cristina (Frontiers in Veterinary Science, 2023)
Small extracellular vesicles (sEV) are a class of extracellular vesicles (30-150 nm), delivering molecules including proteins, metabolites, and microRNAs (miRNAs), involved in physiological intercellular crosstalk and disease pathogenesis. The present pilot study aims are (I) to develop an easy and fast protocol for the isolation of sEV from plasma of mast cell tumor (MCT)-affected dogs; (II) to evaluate if miR-21-5p (sEV-miR-21-5p), a miRNA overexpressed by MCT, is associated with sEV. Seventeen dogs have been enrolled in the study: 4 healthy and 13 (6 with and 7 without nodal metastasis) MCT-affected dogs. sEV were isolated using size exclusion chromatography (SEC) (IZON column 35nm) and were characterized by Western blot, Nanoparticle tracking analysis, and transmission electron microscopy. sEV-miR-21-5p was quantified using digital PCR. sEV expressed the specific markers CD9 and TSG101, and a marker of mast cell tryptase. The sEV mean concentration and size were 2.68E+10 particles/ml, and 99.6 nm, 2.89E+10 particles/ml and 101.7 nm, and 3.21E+10 particles/ml and 124 nm in non-metastatic, nodal metastatic, and healthy samples, respectively. The comparative analysis demonstrated that the level of sEV-miR-21-5p was significantly higher in dogs with nodal metastasis compared to healthy (P=0.038) and without nodal metastasis samples (P=0.007). In conclusion, the present work demonstrated that a pure population of sEV can be isolated from the plasma of MCT-affected dogs using the SEC approach and that the level of sEV-miR-21-5p is higher in nodal metastatic MCT-affected dogs compared with healthy and MCT-affected dogs without nodal involvement.